2014
DOI: 10.1155/2014/290101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Senior Dental Students’ General Attitude towards the Use of Rubber Dam: A Survey among Two Dental Schools

Abstract: The purpose of this study was to evaluate the general attitude of senior dental students towards rubber dam use, specifically focusing on endodontic practices prior to starting to serve community. Questionnaires were distributed to senior year students of a private school and a state school in Istanbul. Questions were asked about areas where the students used rubber dam, its advantages and difficulties, and whether they agreed or disagreed with some aspects of the rubber dam. The private school students rated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
6
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 21 publications
6
23
6
3
Order By: Relevance
“…The main cause of not using the rubber dam was that the asked persons consider it a time consuming procedure and they assume that it causes discomfort for the patient. These answers are similar to other reports, [14] although other studies that actually surveyed patients have found that patients acceptance is high when asked about the rubber dam [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…The main cause of not using the rubber dam was that the asked persons consider it a time consuming procedure and they assume that it causes discomfort for the patient. These answers are similar to other reports, [14] although other studies that actually surveyed patients have found that patients acceptance is high when asked about the rubber dam [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…and Khathoon and Raj. [ 3 6 ] Further, in the present study, 15.5% of the students selected the option to prevent accidental swallowing or aspirating particles or instruments is a major advantage of rubber dam usage. A study conducted by Ahmad et al .…”
Section: Discussionmentioning
confidence: 63%
“…Besides, from a medicolegal aspect, to avert malpractices, it is imperative to use rubber dam; the failure to do so could lead to serious consequences. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Copious studies conducted by Tanalp et al . at America (59% of general dentists and 92% of endodontists),[ 11 ] Whitworth et al . [ 10 ] (only one-fifth of dentists in the UK), Sisir et al .…”
Section: Discussionmentioning
confidence: 99%